2022
DOI: 10.1007/s42690-022-00733-6
|View full text |Cite
|
Sign up to set email alerts
|

Host fruits shape the changes in the gut microbiota and development of Bactrocera dorsalis (Diptera: Tephritidae) larvae

Abstract: Bactrocera dorsalis infests a wide range of host fruits, some of which are suitable hosts, while others are less suitable ones. Although reports highlighted the bacteria-mediated adaptations to different host-fruits, the phenotypic cost and/or gain of the association between insect's gut bacteria and fruit substrates has not been fully studied. In this study, we hypothesized that, when the larvae are confronted with host fruits with different suitability, its community structure changes over time as a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The insect-associated microbial community is dynamic and responsive to various stressors ( Zhang et al, 2022 ). The related microbiota, like the insect, is subject to natural selection pressure, and its composition can be influenced by variables such as dietary changes, food scarcity, and exposure to toxic substances ( Adair and Douglas, 2017 ; Akami et al, 2022 ). The microbiota of hosts exposed to pesticides as a source of selection pressure may also assist the host in metabolizing these substances.…”
Section: Impacts Of Gut Microbiota On the Activity Of Pesticidesmentioning
confidence: 99%
“…The insect-associated microbial community is dynamic and responsive to various stressors ( Zhang et al, 2022 ). The related microbiota, like the insect, is subject to natural selection pressure, and its composition can be influenced by variables such as dietary changes, food scarcity, and exposure to toxic substances ( Adair and Douglas, 2017 ; Akami et al, 2022 ). The microbiota of hosts exposed to pesticides as a source of selection pressure may also assist the host in metabolizing these substances.…”
Section: Impacts Of Gut Microbiota On the Activity Of Pesticidesmentioning
confidence: 99%
“…Moreover, this study showed that the gut bacteria of P. xylostella are potentially related to the food it eats. These indicate a potential correlation between insect gut bacteria and the food they consume, the phenomenon shared with S. frugiperda , Bactrocera dorsalis, and Nezara viridula [ 8 , 28 , 29 , 30 ]. However, studies have shown that both environmental factors and food can affect insect gut microbial diversity [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The direct and indirect colonization resistance from the commensal gut microbiota will limit the long-term effect of the probiotic. Indeed, Akami et al, [42], working on Bactrocera dorsalis, discovered that axenic flies preferred probiotic diets over symbiotic flies, confirming colonization resistance due to resident microbiota. They hypothesize that the native probiotic isolates were able to recolonize their natural habitat in the axenic flies' guts and revive appetitive behaviors that had been slowed due to bacterial suppression.…”
Section: Colonization Of the Probiotics And Host Origin Importancementioning
confidence: 99%